Home and abroad: Racial stereotyping of the Muslim orient in selected of Victorian fiction / Mafaz M. Mustafa - Mafaz M. , Mustafa (2016)
As the aim of the study is to trace the stereotypes of the Muslim and Jewish communities in selected orientalist Victorian texts, it reveals different aspects of Victorian preoccupations and anxieties about the role of England in asserting and spreading civilization at "home" and "abroad". In light of the historical and political events in both the Middle East and Victorian England, the study distinguishes the era for its complexity and inevitable contribution to the political order of the day in the way it confirms or challenges set stereotypes. Using Homi Bhabha’s theoretical framework, the recirculation of negative stereotypes stabilized certain impressions of the Muslim orient while also challenging old stereotypes of the Jewish orient. The significance of the study lies in its attempt to bridge the gap between previous scholarship on the portrayal of the Muslim Orient and studies that focus on Victorian concerns and ideals. It is also significant in highlighting the way Victorian racial stereotypes contributed to the escalating racism in the political order of the world of today, which culminated in the contemporary crises of the Arab Spring. This study consists of an introductory chapter, three body chapters and a concluding chapter. Chapter One on Victorian women writers and Victorian aesthetics, examines the anxieties present in the captivity narratives of Emma Roberts’ “The Florentines” and selected tales of Julia Pardoe’s The Romance of the Harem, which were used as a vehicle for the emancipation of Victorian women in Charlotte Bronte’s Jane Eyre before the New Woman movement. Using Sir Walter Scott’s historical romances as the background for challenging the stereotypes of Muslims and Jews in The Talisman and Ivanhoe, Chapter Two examines the extent to which Benjamin Disraeli’s Alroy, Edward B. Lytton’s Leila or The Siege of Granada and Hall Caine’s The Scapegoat challenge Scott’s stereotypes, with the aim of highlighting how the historical events in these works reflect on the domestic tensions in England pertaining to the Jewish Question. Chapter Three focuses on the Victorian political novel in which the cause of Jewish emancipation is dramatized in Disraeli’s Tancred, Anthony Trollope’s The Prime Minister and George Eliot’s Daniel Deronda both at "home" in England and "abroad" in Palestine. The development in the representation of the Muslim and Jewish communities in the three body chapters reflect a "fixed" portrayal of the Muslim Orient in contrast to the more "fluid" Jewish orient, the aim of the authors' being to establish the superiority of the latter as a race and a nation in a country of their own, as representatives of the English "abroad". Applauded by the British Empire then and the United States of America today, the impact and influence of such stereotyping of these two communities in the literature of the Victorian era is seen in the way they persist and flourish in the popular culture of today.